COVID-19 and emergency remote learning and teaching: A mixed methods analysis of the mental well-being of academics at a higher education institution in South Africa - Crowley, T.; Onwuegbuzie, A.J.; Ojo, E.O.; Burger, A.; Bergsteedt, B. J.; Adams, S. P. (South African Journal of Higher Education, 2025)
The purpose of this study was to investigate how academics at a South African higher education institution (HEI) adapted to emergency remote learning during the COVID–19 pandemic and how it affected their mental well–being. Using a concurrent mixed methods equal status design, an online survey was completed by 248 academics, which included demographic data, the 12–item General Health Questionnaire (GHQ–12) to measure mental well–being, and open–ended questions. Slightly more than one half of academics (54.1 per cent) reported losing much sleep and 81.4 per cent reported that they were under stress. Further, 28.6 per cent of participants had feelings of being unhappy or depressed and 31.1 per cent reported losing confidence. Almost one third of academics (31.9 per cent) had GHQ–12 threshold scores above 3 that is indicative of a mental health problem. A principal components analysis yielded two sub–scales: Perceived Mental Health (distress/anxiety) and Adaptive Behaviours (social function). In our study, being a woman, permanently employed, not having children, and being a lecturer were associated with lower perceived mental health; also, being permanently employed and living alone were associated with lower adaptive behaviours. In the context of ongoing online learning pedagogies and working from home, the mental well–being of academics in HEIs should be effectively supported, with differentiated/tailored/personalised approaches.